Weed management in irrigated wheat (Triticum aestivum) with special reference to buttercup weed (Ranunculus spp) in north-west Himalayas - Singh, Raman Jeet (The Indian Journal of Agricultural Sciences, 2012)
An on-farm trial was conducted at five farmer fields of Bageshwar district of Uttrakhand to validate, refine and popularize the technology developed by VPKAS, Almora for managing Buttercup (Ranunculus spp) during 2007–10. The aim of the study was to find out the effectiveness of 2,4-D @ 1.0 kg ai/ha, isoproturon @ 1.0 kg ai/ha and tank mix application of 2,4-D @ 0.5 kg ai/ha with isoproturon @ 1.0 kg ai/ha over farmers practice of hand weeding twice at 30 and 60 DAS and unweeded control on the infestation of weeds and profitability of wheat (Triticum aestivum L. emend. Fiori and Paol.). Tank mix application of 2, 4-D+isoproturon (0.50+1.0 kg/ha) at 35-40 DAS reduced the density and dry weight of Ranunculus and other weeds and nutrient uptake by weeds (3.9 kg N, 0.9 kg P and 6.2 kg K/ha) compared to farmers practice. This combination also resulted in 12.5% higher grain yield, nutrients by wheat (73.5 kg N, 11.6 kg P and 60.0 kg K/ha) and net returns (` 19 030/ha) With this technology, drudgery reduction of about 475-man days/ha can be made possible, which could be used in other fruitful activities of hilly farmers, particularly women.